Cellular distribution of B-raf protein kinase in the brainstem of the adult rat. A fluorescent immunohistochemical study - Mihály, András (Acta Biologica Szegediensis, 2007)
The Raf-kinases can be activated by growth factors, cytokines and neurotransmitters. Previous studies in our laboratory proved the presence of Raf proteins in the neurons and astrocytes of the forebrain. The present study investigated the localization of B-Raf protein in the brain stem of the rat. Use was made of polyclonal anti-B-Raf serum which detected B-Raf molecules in our Western blotting experiments. Monoclonal tyrosine hydroxylase and dopamine-G-hydroxylase antibodies were used to identify catecholaminergic brainstem nuclei and to study the co-localization of B-raf protein in them. We found the widespread distribution of B-raf-protein-like immunoreactivity in every segment of the brainstem. Mainly neurons were stained, but weakly immunoreactive glia-like cells were observed, too. Strongest staining was detected in the motor cranial nerve nuclei, the giant neurons of the reticular formation and in the raphe nuclei. The catecholaminergic structures displayed medium-to-weak B-raf-like immunoreactivity. The neurons of the locus ceruleus and the substantia nigra stood out with a conspicuous B-raf-like immunoreactivity. The B-raf protein was localized in the perinuclear cytoplasm and in thick, dendrite-like processes. The ubiquity of 3-raf kinase suggests its important contribution to the regulation of the normal cell cycle in these neurons.